Representasi Nilai-Nilai Moderasi Beragama dalam Buku Teks Pendidikan Agama Islam Kelas VII Tingkat SMP Kemendikbud Kurikulum Merdeka - Sholeh Effendi; Fadia Nur Haya; Khuriyah Khuriyah (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study aims to analyze the representation of religious moderation values in the Islamic Religious Education (PAI) textbook for grade VII at the junior high school level published by the Ministry of Education and Culture in the Merdeka Curriculum. The research method used in this research is a qualitative approach with descriptive research type. Data collection techniques are carried out through literature review and document analysis. This research will also use triangulation techniques to ensure data accuracy. The results show that this textbook successfully conveys the values of religious moderation in a way that is appropriate to the Indonesian context which is rich in diversity. The value of national commitment is emphasized through teaching about the importance of maintaining national unity, while the value of tolerance and interfaith cooperation is reflected in materials that respect differences in beliefs and invite students to coexist peacefully. In addition, the value of anti-violence in religion is also integrated by promoting the principles of peace and compassion, as well as attitudes that avoid extremism. The book also introduces respect for local cultures that are in line with religious principles, to create a society that is inclusive, peaceful, and able to maintain social harmony. Thus, PAI textbooks in the Merdeka Curriculum not only function as a tool for religious learning, but also as a means of building student character that emphasizes the values of religious moderation in everyday life.